1990
DOI: 10.5694/j.1326-5377.1990.tb125266.x
|View full text |Cite
|
Sign up to set email alerts
|

Skin cancer in Geraldton, Western Australia: a survey of incidence and prevalence

Abstract: A survey of the incidence and prevalence of non‐melanocytic skin cancer in Geraldton, Western Australia, was undertaken in November 1987. All residents aged 40 to 64 years whose names were on the electoral roll on August 1, 1987 were invited to undergo a whole‐body skin examination by a dermatologist. When a skin cancer was suspected, participants were referred for treatment to their usual medical practitioner. Subjects were asked to recall incident skin cancers over the preceding two years, and medical record… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

6
58
1

Year Published

1992
1992
2014
2014

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 98 publications
(65 citation statements)
references
References 16 publications
(4 reference statements)
6
58
1
Order By: Relevance
“…The trend for the trunk to be a common site for BCCs has been detected in other surveys in Australia (Green, 1982;Kricker et al, 1990;Giles et al, 1988) and is believed to be due to a change in fashion and sun-exposure habits.…”
Section: Discussionsupporting
confidence: 54%
See 1 more Smart Citation
“…The trend for the trunk to be a common site for BCCs has been detected in other surveys in Australia (Green, 1982;Kricker et al, 1990;Giles et al, 1988) and is believed to be due to a change in fashion and sun-exposure habits.…”
Section: Discussionsupporting
confidence: 54%
“…100,OO in the subtropical north (Kricker et at., 1990) and 1,153 in the tropics (Stenbeck et al, 1990).…”
mentioning
confidence: 99%
“…In two studies, random biopsies of clinically diagnosed AKs were carried out and it was found that the diagnosis was incorrect in 15% of the cases in one study and in 19% of the cases in another. 11,12 In the latter study, the authors claimed that up to 25% of the AKs disappeared. In a third study, three dermatologists could not agree on the diagnosis in 16% of the cases and the authors claimed that 19% of AKs disappeared.…”
Section: Discussionmentioning
confidence: 95%
“…[9][10][11] Causes of BCC involve UV induced or inheritable p53 or patched gene mutations. [41][42][43] p53 mutations result in the loss of cell arrest and hence damaged cells are not repaired or deleted.…”
Section: Discussionmentioning
confidence: 99%
“…[9][10][11] They are derived from aberrant keratinocytes possibly related to follicular epithelium. White individuals are most frequently affected and are most at risk between 40 and 79 years of age.…”
mentioning
confidence: 99%